Consumer Purchase Preferences of Medan City Residents in using Fintech Payment and Consumer Behavior in the Digital Era: Preferensi Keputusan Pembelian Masyarakat Kota Medan dalam menggunakan Fintech Pembayaran dan Perilaku Konsumen di Era Digital - Violyne August Simson; Elisabeth Nainggolan (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study examines the influence of financial technology (fintech) and consumer behavior on consumer purchase preferences in Medan City in the digital era. The method used is a quantitative approach with a survey of 100 respondents in Medan who routinely use digital wallet applications, as well as data analysis using Partial Least Squares (PLS) through SmartPLS software. The results showed that fintech had a positive and significant effect on purchase preferences with a path coefficient of 0.374 (p = 0.003, f² = 0.181), while consumer behavior had a stronger impact with a coefficient of 0.455 (p = 0.000, f² = 0.268). The two variables together explain the 57.4 % variability of purchasing decision preferences (R² = 0.574), with strong predictive relevance (Q² = 0.510). The results of this study show that the integration of fintech payment and consumer behavior together contributes significantly to consumer purchase preferences in the Medan City. Practical recommendations from the study include improving digital and financial literacy through integrated education programs for all levels of society, as well as simplifying the e-money application interface to make it more intuitive and accessible.